Marcadores da pré-hipertensão: revisão sistemática da literatura - Peres, Jorge Alexandre de Araujo (2020)
Introduction: The identification of biomarkers linked to the etiopathogenesis of prehypertension, with adequate predictive value and good cost-benefit ratio, would contribute to the early diagnosis and prevention of more severe forms of hypertension, involving cardiovascular outcomes. Therefore, the aim of this study was to carry out a systematic literature review, to identify the main clinical evidence related to the use of biomarkers for the prehypertension stage diagnosis in adults. Methods: A systematic search was performed in the PUBMED database, using the following strategy: (prehypertension [majr] OR "pre-hypertension" [majr] OR "(pre) hypertension" [majr] OR "(pre-) hypertension" [majr]) AND (biomarkers OR markers) AND blood NOT (diet OR intake). The review was conducted according to the PRISMA protocol (Preferred Reporting Items for Systematic Reviews and Meta-analyzes). Results: The search, carried out on June 30, 2020, returned 71 papers. After reading the titles and abstracts, 31 articles were eliminated according to eligibility criteria, especially for not effectively discussing the use of markers for prehypertension diagnosing in adults, that discusses only hypertensive individuals, for using samples with a different age range than that established for the present study, or even for not shown a clear division between patients with or without prehypertension. The remaining 40 studies, considered for review, totalized 70,967 patients. Conclusion: The most promising and reliable marker of prehypertension is serum uric acid, followed by serum gamma-glutamyltransferase. Based on these results, the evaluation of these markers, especially uric acid, can be used to complement the screening process of pre-hypertensive patients.